AWARENESS, ATTITUDE AND PRACTICES TOWARDS COVID-19 AMONG IIUM STUDENTS - Nur Izzati Ariffin; Siti Hajar Mohd Badrol; Siti Aida Aliah Mohd Azlan; Faridah Hussain (INTERNATIONAL JOURNAL OF LAW, GOVERNMENT AND COMMUNICATION (IJLGC), 2024)
The rise of the COVID-19 pandemic has killed more than two million people within a year. The deadly virus brings chaotic problems to every layer of society, including university students. The main goal of this study is to investigate the awareness regarding COVID-19 among International Islamic University of Malaysia (IIUM) students. This study examines the awareness, perception, and involvement of the IIUM community to mitigate the spread of COVID-19 during the scare. A qualitative research design was employed, using an interview method through purposive sampling procedure as the research instrument used for the data collection. A total of eight respondents, including international and local university students, participated in the study. The study adopted the situational theory of publics by Grunig (1966) to guide the study. This study found that IIUM local students have adequate information and awareness regarding COVID-19. However, future efforts should be aimed at enhancing awareness campaigns among the IIUM international students in Malaysia. The findings of the study will have implications on awareness, perception, and behaviour during a virus outbreak.